Comparative Analysis of Students' Environmental Awareness Attitudes in Learning at Adiwiyata and Non-Adiwiyata Schools - Sri Amini; Hastuti Hastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The environment is a space inhabited by living things along with biotic and abiotic elements that interact to maintain ecological balance. This study aims to compare the environmental awareness attitudes of Adiwiyata and non-Adiwiyata high school students in Boyolali Regency. This study is motivated by the important role of education in fostering environmental awareness to prevent ecosystem degradation. The sample consisted of two schools, namely SMA Negeri 1 Ampel (Adiwiyata) and SMA Negeri 1 Cepogo (non-Adiwiyata) which were selected randomly. Data were collected using a questionnaire and analyzed using the Independent Samples t-test and the Mann-Whitney U-test. The results showed a significant difference in students' environmental awareness attitudes between the two schools. Students in Adiwiyata schools showed more positive attitudes towards cleanliness, energy conservation, waste management, and maintaining the quality of the school environment compared to students in non-Adiwiyata schools. This difference is caused by the integration of the Adiwiyata program into school policies, curriculum, and environmentally friendly activities that involve the active participation of school residents. The Adiwiyata program makes a positive contribution in shaping environmental awareness among students, by emphasizing the importance of implementing environmental education systematically in Adiwiyata and non-Adiwiyata schools to support sustainable development